STRATEGI PENGENDALIAN DISORIENTASI SISWA DALAM BELAJAR DI SEKOLAH - Muhammad Misdar (Conciencia, 2017)
Student learning situations in schools do not always benefit psychologically for certain students and teachers, because there are attitudes and behaviors of students that show contradiction with should occur. Ideally, the student should seriously study but is sometimes shown by aberrant behavior. Student learning orientation should focus on achieving success, get maximum achievement in a school, but sometimes fact justeri on the contrary, studying student no more just doing duty for the sake of pleasing parent and reach social status finished school. What is described above, the emergence is not without cause, the attitude of disorientation of students' learning in school is basically sourced from internal students themselves rather than from external factors. Students' disorientation in learning does not just appear, but arises from a cause, among them is the negative cycle of academic development experienced by students, low perceptions of learning, and effort in learning is very low. The adverse effects of these three factors will also affect students' attitudes toward learning, such as the use of ego in learning is greater than the logic, avoidance of challenges, such as dislike of difficulties, because it does not like to something hard and become a heavy burden for the brain , So can not measure the success and failure in learning. The consequences of it all have an effect on their behavior, such as tend to be difficult   to   control   to   learn   by   the   teacher, ignorance of the teacher and the lesson, likes to belittle the lesson learned, the less attention to the lesson   and   sometimes   show   the   destructive behavior when facing the  excessive challenge in learning, So the challenge he likes to be physically fit is not an intellectual challenge. In order to provide solutions to the attitudes and behaviors of students as described above, there needs to be a breakthrough that can be done, at least can be done through two kinds of strategies, namely motivation strategy and emotional strategy. Both are solutions that are internal rather than external.